The Use of Role Play as Model of Community Service Program in Sukahaji Village West Bandung Regency - Jalu Rafli Ismail; Anisa Karima (WARTA LPM, 2021)
Community service is the integral part to tertiary education in Indonesia, as emphasized by Three Pillars of Tertiary Education (Tri Dharma Perguruan Tinggi) which consist of education, research, and community service. According to Article 47 verse (1) and (3) of Law 12/2012 on Tertiary Education, community service is conducted to implement and internalize science and technology in order to advance general prosperity and develop nation’s intellectual life. Community service is also applied as a lesson to maturate academics. This study is conducted to report how community service could be done in a role play method to meet the ideals set in the law. The study is based on community service program done by Geography Students Association in Sukahaji Village, Cipeundeuy sub-district, West Bandung Regency, where students are grouped to take part into local resident life of various occupations. The result of this study shows that 65% of local residents said that student role play model in community service is helpful for their daily activities, while 70% of students said that role play model in community service has motivated them on improving their understanding of communal life and raised social awareness.